2021
DOI: 10.6004/jnccn.2020.7621
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Durvalumab After Chemoradiotherapy in Unresectable Stage III NSCLC: A US Healthcare Perspective

Abstract: Background: Durvalumab was approved by the FDA in February 2018 for patients with unresectable stage III NSCLC that has not progressed after platinum-based concurrent chemoradiotherapy (cCRT), and this regimen is the current standard of care. The objective of this study was to examine the cost-effectiveness of durvalumab following cCRT versus cCRT alone in patients with locally advanced, unresectable stage III NSCLC. Methods: A 3-state semi-Markov model was used. Modeling was performed in a US healthcare setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Numerous cost-effectiveness analyses have been published based on both the ITT and the PD-L1 TC ≥ 1% PACIFIC populations. These analyses report a lower range of QALY gains with durvalumab therapy (0.24-1.32 for the PD-L1 TC ≥ 1% population) compared with the original company base-case analysis (2.93) (Table 3 in the ESM) [30,31,[44][45][46][47][48]; this could be explained, in part, by the use of different modelling approaches, decision problems, and/or assumptions regarding long-term survival benefit. The recently published data from PACIFIC (March 2020 DCO) demonstrated a gain in median OS of 27.8 months with durvalumab therapy versus placebo and a sustained OS and PFS benefit with durvalumab at 4 years (PD-L1 TC ≥ 1% population) [34]; the 48-month OS rates were 55 and 38% with durvalumab and placebo, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous cost-effectiveness analyses have been published based on both the ITT and the PD-L1 TC ≥ 1% PACIFIC populations. These analyses report a lower range of QALY gains with durvalumab therapy (0.24-1.32 for the PD-L1 TC ≥ 1% population) compared with the original company base-case analysis (2.93) (Table 3 in the ESM) [30,31,[44][45][46][47][48]; this could be explained, in part, by the use of different modelling approaches, decision problems, and/or assumptions regarding long-term survival benefit. The recently published data from PACIFIC (March 2020 DCO) demonstrated a gain in median OS of 27.8 months with durvalumab therapy versus placebo and a sustained OS and PFS benefit with durvalumab at 4 years (PD-L1 TC ≥ 1% population) [34]; the 48-month OS rates were 55 and 38% with durvalumab and placebo, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Till now, there has not been any economic research on durvalumab in China, and a total of 6 economic studies on durvalumab versus BSC have been retrieved out of China, with 3 from US and 1 each from Switzerland, Italy and UK [11][12][13][14][15][16]. The clinical data of these six studies were obtained from PACIFIC study with the same control group of BSC (Table 4).…”
Section: Plos Onementioning
confidence: 99%
“…These studies were varied in the target population, study perspectives, models, clinical background and resources of cost data, hence different conclusions were drawn. The US study [11] US study [12] US study [13] Switzerland study [14] Italy study [15] UK study [16] Present study �…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated the cost-effectiveness of durvalumab, and although funding varies across different countries, the overall conclusion is that durvalumab consolidation treatment is cost-effective compared to combined chemoradiotherapy alone, accentuating the importance of increased access. [68][69][70] Cost-effectiveness analysis has shown no consolidation therapy resulted in a mean cost of US $185,944 and mean quality-adjusted life-years of 2.34. Durvalumab consolidation increased quality-adjusted lifeyears to 2.57, with an increase in mean cost to $201,563.…”
Section: Cost Of Durvalumab For Stage III Nsclcmentioning
confidence: 99%